2017
DOI: 10.1158/1078-0432.ccr-17-1434
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Response Dynamics of Advanced Non–small Cell Lung Cancer Patients Treated with PD-1 Inhibitors: Imaging Markers for Treatment Outcome

Abstract: Purpose We evaluated tumor burden dynamics in advanced non-small-cell lung cancer (NSCLC) patients treated with commercial PD-1 inhibitors to identify imaging markers associated with improved overall survival (OS). Experimental Design The study included 160 advanced NSCLC patients treated with commercial nivolumab or pembrolizumab monotherapy as a part of clinical care. Tumor burden dynamics were studied for the association with OS. Results Tumor burden change at best overall response (BOR) ranged from −10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
48
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 38 publications
6
48
0
1
Order By: Relevance
“…In a previous clinical trial of nivolumab, the frequency of radiologic pseudoprogression was approximately 5%. 10 More recent reports have shown that the frequency of radiologic pseudoprogression was 0% to 5% in real-world settings, 6,11,12 which is similar to our findings. However, to the best of our knowledge, our cohort was the largest to reveal the incidence of radiologic pseudoprogression in relatively small patient subsets.…”
Section: Discussionsupporting
confidence: 91%
“…In a previous clinical trial of nivolumab, the frequency of radiologic pseudoprogression was approximately 5%. 10 More recent reports have shown that the frequency of radiologic pseudoprogression was 0% to 5% in real-world settings, 6,11,12 which is similar to our findings. However, to the best of our knowledge, our cohort was the largest to reveal the incidence of radiologic pseudoprogression in relatively small patient subsets.…”
Section: Discussionsupporting
confidence: 91%
“…The shift in focus from the direct targeting of the cancer cell towards the stimulation of the anti-tumor response has resulted in encouraging clinical results in humans, but also comes with new problems. Despite promising overall response rates (ORR) for treatment with CPIs, tumor vaccines and ACT or a combination of these, response rates to immunotherapy vary greatly between tumor subtypes, depending partly on their immunogenicities [30,[35][36][37][38][39][40][41][42][43][44]. Primary therapy resistance, defined as a lack of clinical benefit from immunotherapy on tumor growth, exists in a large proportion of patients.…”
Section: Limitations Of Immunotherapymentioning
confidence: 99%
“…Immune-related tumor response and progression.-ICI therapy may lead to unique patterns of tumor response and progression at imaging in subsets of patients. The most welldescribed pattern is pseudoprogression, which includes (a) response after an initial increase in tumor burden, and (b) respose during or after the appearance of new lesions (36,37,(54)(55)(56)(57)(58). Although pseudoprogression is becoming increasingly known, it is important to recognize the low incidence of pseudoprogression, especially in patients with NSCLC treated with PD-1/PD-L1 inhibitors, with the frequency ranging from 0.6% to 5% (41,57,59).…”
Section: Pitfalls Of Image Interpretations For Lung Cancer Precision mentioning
confidence: 99%
“…The most welldescribed pattern is pseudoprogression, which includes (a) response after an initial increase in tumor burden, and (b) respose during or after the appearance of new lesions (36,37,(54)(55)(56)(57)(58). Although pseudoprogression is becoming increasingly known, it is important to recognize the low incidence of pseudoprogression, especially in patients with NSCLC treated with PD-1/PD-L1 inhibitors, with the frequency ranging from 0.6% to 5% (41,57,59). While imaging strategies that help reliably differentiate pseudoprogression from true progression in the early course of therapy remain to be established, accumulating evidence of the low incidence of pseudoprogression in patients with NSCLCs indicates that an increase in tumor burden is more likely to reflect true progression than pseudoprogression in most patients (36).…”
Section: Pitfalls Of Image Interpretations For Lung Cancer Precision mentioning
confidence: 99%